3D bioprinted glioma cell‐laden scaffolds enriching glioma stem cells via epithelial–mesenchymal transition. Issue 2 (22nd October 2018) - Wang, Xuanzhi; Dai, Xingliang; Zhang, Xinzhi; Ma, Cheng; Li, Xinda; Xu, Tao; Lan, Qing
Abstract: Glioma stem cells (GSCs) are thought to be the root cause of tumor recurrence and drug resistance in glioma patients. In‐depth study of GSCs is of great significance for developing the treatment strategies of glioma. Unfortunately, it is difficult and takes complicated process to obtain GSCs. Therefore, establishing an ideal in vitro model for enriching GSCs will greatly promote the study of GSCs. In this study, the stemness properties of glioma cells were enhanced in three‐dimensional (3D) bioprinted tumor model. Furthermore, the possible molecular mechanism of GSCs enrichment: epithelial–mesenchymal transition (EMT) was explored. Compared with two‐dimensional cultured cells, the proportion of GSCs and EMT‐related genes in 3D cultured cells were significantly increased. Moreover, the 3D cultured glioma cells with improved stemness properties resulted in higher drug resistance in vitro and tumorigenicity in vivo . Taken together, 3D bioprinted glioma cell‐laden scaffold provides a proper platform for the enrichment of GSCs and it is expected to further promote the research on glioma drug resistance. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 383–391, 2019.